Identification and Risk Management In The Expenditure Process: Risks Leading to Deadline Slippage and Costs, and Building Projects - Challal, Abdelhak; Tkiouat, Mohamed (Gadjah Mada International Journal of Business, 2013)
The objective of this research is the design of a mapping of risks which are mainly related to the processes of expenditure. The research also serves to identify the actions and the necessary measures to control risks and the delays of completing a construction project. The literature from the last two decades related to this field was examined. A quantitative analysis of risks in the expense process of building projects sample representing various regions of Morocco allows identifying the risks and ranking them by determining their occurrences and impacts. Eight major risks, 43 measures, 52 actions and 10 performance indicators are linked to these risks have been identified.